Efficacy of oral intake of haruan [Channa striatus (Bloch, 1793)] extract versus glucosamine sulfate on knee osteoarthritis - Abdul Kadir, Azidah (2019)
Knee osteoarthritis (OA) is the most prevalent degenerative arthritis and currently there are no pharmacological agents that able to retard the disease progressions. Channa striatus (CS) is a freshwater fish and its potential for treating knee OA has been explored but no comparison study has been done with glucosamine (GlcN), which has been widely used to treat osteoarthritis. In vivo study was conducted to evaluate the efficacy of CS extract versus GlcN on histomorphometric examinations in experimental OA rabbit model and a clinical trial was done to assess the efficacy of different doses of CS extract versus GlcN on primary knee osteoarthritis patients in terms of knee OA symptoms based on Western Ontario and McMaster University Osteoarthritis Index (WOMAC), analgesic drug consumption, serum cartilage oligomeric matric protein (COMP), cyclooxygenase 2 (COX-2) enzyme and serum Prostaglandin E2 (PGE2). OA was induced using Anterior Cruciate Ligament transection in thirty three rabbits and were divided into three groups namely: CS, GlcN and control group. The CS and GlcN groups were orally administered with 51.4 mg/kg of CS extract and 77.5 mg/kg of GlcN sulphate respectively based on the dosage used for human study for eight weeks. The articular cartilage was evaluated macroscopically and histologically using semi-quantitative and quantitative methods. One-way analysis of variance (ANOVA) was used to analyse the histologic assessment and Kruskall Wallis test was used to analyse the macroscopic grading. A randomized, double-blind, placebo-controlled trial comparing the effects of oral CS extract at the dose rate of 1000mg/day or 500mg/day, 1500mg/day of glucosamine sulphate and placebo among knee OA patients for 6-month intervention period was conducted. Repeated measures analysis of covariance and variance was used to analyse the WOMAC index. One-way ANOVA was used to analyse the analgesic score, COMP, COX-2 and PGE2 level. The results revealed that the severity of macroscopic score was significantly less in CS as compared to GlcN (p<0.05) group. CS exhibit less severity of semi-quantitative histology score compared to control (p<0.05) in more compartments of the joints compared to GlcN. Both CS (p<0.05) and GlcN (p<0.05) groups demonstrated higher cartilage thickness and area; lower roughness than control group. Moreover, less cartilage roughness was expressed in CS group compared to the GlcN group (p<0.05). In the clinical trial, 153 patients were analysed. Both CS (p<0.05) and GlcN (p<0.05) groups demonstrated significant improvement of WOMAC stiffness and physical function compared to placebo. CS (1000mg/day) (p<0.05), CS (500mg/day) (p<0.05) and GlcN (p<0.05) groups reduced serum COX-2 level compared to placebo. Serum PGE2 was reduced in CS (1000mg/day) (p<0.05) compared to placebo. In conclusion, it was found that based on macroscopic, semi-quantitative and quantitative histological examination, CS extract was superior to GlcN in maintaining the structure of the cartilage degeneration on an ACLT OA-induced rabbit model. In the clinical trial, both doses of CS extract had similar efficacy with GlcN in alleviating the symptoms of knee OA and had an anti-inflammatory effect through the reduction of serum COX-2. CS administered at the dose rate of 1000mg/day was effective in reducing PGE2 level compared to GlcN.